The Effect of Pioglitazone on Antioxidant Levels and Renal Histopathology in Streptozotocin-Induced Diabetic Rats. (9th May 2013) - Kuru Karabas, Munire; Ayhan, Mediha; Guney, Engin; Serter, Mukadder; Meteoglu, Ibrahim
Abstract : Objective . Diabetic nephropathy is the most commonly seen cause of chronic renal failure, and oxidative stress is important in etiology. In the present study, favorable effects (if any) of the treatment with a thiazolidinedione group drug, pioglitazone, on antioxidant enzyme levels in the renal tissue, renal histopathology, and inflammatory cytokine levels have been investigated. Method . Forty male Wistar rats were divided into 4 groups as the control, diabetic control, and 10 and 30 mg pioglitazone-administered diabetic groups. After 4 weeks, antioxidant enzyme levels in renal tissues and inflammatory markers were investigated. Results . Blood glucose levels did not differ between the diabetic control and drug-administered groups. In pioglitazone-administered rats, histopathological findings such as tubular dilation, necrotic tubular epithelium, glomerular focal necrosis, and vascular consolidation were observed at a lesser extent than the diabetic control group. Any difference was not detected between the diabetic groups with respect to the levels of malondialdehyde, superoxide dismutase, catalase, glutathione, nitric oxide, interleukin-6, and tumor necrosis factor-alpha. Conclusion . Pioglitazone regressed development of histopathological lesions such as glomerular focal necrosis, tubular epithelial necrosis, tubular dilation, and vascular wall consolidation. However, any favorable effect on antioxidant enzyme levels in renal tissues and inflammation markers was not detected.